9 Stat. at Large of Pa. 347, ch. 836, § 4 (1903) - (:unkn) unknown (General Publisher, 1779)
Prohibited firearm possession for people “disaffected to the liberty and independence” of the state, empowered officers to disarm any person who did not take an oath.
--
Keywords: LOYALTY OATH REQUIRED